102 Early Angiography and Coronary Intervention in Comatose Survivors of Out of Hospital Cardiac: Can the 12-lead ECG be Gatekeeper?. (3rd June 2016) - Rahbi, Hazim; Kandan, Raveen; Baumbach, Andreas; Cowburn, Philip; Thomas, Matt; Rooney, Kieron; Johnson, Tom; Strange, Julian
Abstract : Background: Emergency coronary angiography in comatose survivors of out of hospital cardiac arrest (OHCA), in the absence of STEMI criteria on a post-resuscitation ECG, is controversial. High mortality and the implications on resource use, without robust criteria for the selection of appropriate candidates, has prevented clear guidance from the national societies. Our institution has adopted early involvement of a specialist team, consisting of an interventional cardiologist, emergency care physician and intensive-care anaesthetist, to initiate early assessment of patients. All survivors of OHCA, without an obvious non-cardiac aetiology, are transferred to the cardiac catheterisation laboratory for emergent angiography and intervention, if indicated, irrespective of presenting ECG, before admission to intensive care. We report the outcomes of this pathway with particular emphasis on the predictive value of the post-resuscitation ECG. Methods: We retrospectively reviewed the clinic data, ECG characteristics and angiographic images of all survivors of OHCA admitted to our institution between 1 October 2012 and 31 July 2015. Results: We obtained data for 192 patients (80% male, average age 62 years). 24% patients were transferred from neighbouring hospitals. The median time interval from admission to the emergency department and transfer to the catheter laboratory was 76 min for local patients compared to 176 min for transferred patients. The prevalence of significant coronary artery disease (>70% stenosis in at least one coronary artery) was 77% in our patient cohort. 69 (36%) patients had an acute coronary occlusion whereas 55 (29%) cases were chronic total occlusions. Immediate PCI was undertaken in 109 (57%) cases and of these 46 (42%) did not have ST elevation on the post-resuscitation ECG. Our overall rate of survival to discharge was 58%, with higher rates of survival observed in those undergoing PCI (63% v 52% in conservatively managed patients (non-significant p = 0.1)). Conclusion: Clinical criteria and electrocardiographic data are poor predictors of significant coronary artery disease and acute coronary occlusion. In our experience early involvement of a specialist team to facilitate prompt assessment and immediate coronary angiography is associated with a favourable outcome in this unselected population of comatose survivors of out of hospital cardiac arrest.